2013
DOI: 10.1002/adfm.201300417
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Er3+ Infrared Photoluminescence Embedded in a Hybrid Organic‐Inorganic Copolymer containing Octahedral Molybdenum Clusters

Abstract: Luminescent hybrid copolymers are obtained by copolymerizing in bulk methylmethacrylate with a methacrylic acid (MAC) solution containing [n‐Bu4N]2[Mo6Br8(MAC)6], and aliquots of an Er(TMHD)3 complex (TMHD for 2,2,6,6‐tetramethyl‐3,5‐heptanedione) solution. This leads to novel homogeneous and transparent hybrid materials in which the Er3+ infrared luminescence at 1.55 μm, a standard wavelength for telecommunication applications, is up to six time more intense in the presence of Mo6 clusters when samples are ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…Since the energies of these bands are similar for Mo 6 Cl 14 2− and Mo 6 Br 14 2− , it is believed that both highest occupied and lowest unoccupied molecular orbitals are largely metal centered [61]. Other researchers have revealed that Mo 6 NCs can be integrated with other material systems, such as semiconducting quantum dots [46], silica [47] and copolymer [48]. In an earlier effort, Grasset et al [46] presented the preparation and characterization of a novel organosol and solid state nanocomposite, namely (( n -C 4 H 9 ) 4 N) 2 Mo 6 Br 14 @ZnO, by using an original and simple bottom-up process.…”
Section: Synthesis Approaches For Pt Mo Bi and Alloy Ncsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the energies of these bands are similar for Mo 6 Cl 14 2− and Mo 6 Br 14 2− , it is believed that both highest occupied and lowest unoccupied molecular orbitals are largely metal centered [61]. Other researchers have revealed that Mo 6 NCs can be integrated with other material systems, such as semiconducting quantum dots [46], silica [47] and copolymer [48]. In an earlier effort, Grasset et al [46] presented the preparation and characterization of a novel organosol and solid state nanocomposite, namely (( n -C 4 H 9 ) 4 N) 2 Mo 6 Br 14 @ZnO, by using an original and simple bottom-up process.…”
Section: Synthesis Approaches For Pt Mo Bi and Alloy Ncsmentioning
confidence: 99%
“…Recently, a simple method to obtain Mo 6 –PMMA copolymer samples within which Mo 6 clusters keep their intrinsic luminescence properties has been reported [48]. These emissive properties have been used successfully to sensitize Er 3+ complex emission in the infrared region and within the polymer matrix.…”
Section: Synthesis Approaches For Pt Mo Bi and Alloy Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Face-capped Mo 6 X i 8 X a 6 units containing octahedral molybdenum clusters are the basic buildings blocks of many inorganic solid state compounds, hybrid frameworks and nanomaterials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Formation of Mo 6 cluster occurs at high temperatures via solid state reactions.…”
Section: Introductionmentioning
confidence: 99%
“…They are the first hexanuclear niobium and tantalum cluster compounds showing luminescence properties. They might have high potential for photochemical applications [34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%